PENANGGULANGAN KEMISKINAN DI SEKTOR PERTANIAN: KASUS PADA PROGRAM BEKERJA - Gunawan, Endro; Irawan, Bambang (Analisis Kebijakan Pertanian, 2021)
In order to reduce poverty in the agricultural sector, the Ministry of Agriculture implements the BEKERJA program, which is an effort to empower poor farmers in farming multi-commodities, including laying hens, vegetables, fruit and plantation crops. The objective of this study is to understand the role of the program on increasing farmers' income and reducing poverty. This research was conducted in 11 provinces covering 38 districts which were the location of the BEKERJA program in 2018 and 2019. The data used were primary data collected through in-depth interviews of farmers participating in the program. The results of quantitative and qualitative descriptive analysis concluded that the program was quite successful in enhancing agricultural business activities among poor farmers, but it had not been able to increase farmers' income significantly. The number of poor farmers participating in the program only decreased by 1.48%. There are many challenges faced in empowering poor farmers, and therefore a strong commitment is needed to reduce poverty in the agricultural sector. To increase the effectiveness of these poverty reduction efforts, the empowerment of poor farmers in the future should be carried out as the following: (1) commodities developed are focused on the laying hens and vegetables farming, (2) farmers empowerment and provision of agricultural facilities should be continued at least until the farming activities is financially profitable, (3) technical guidance for cultivation should be strengthen, (4) beneficiaries of the program should be prioritized to young farmers, and (5) development a special program that is focused for the poor farmers.  ABSTRAKDalam rangka menanggulangi kemiskinan di sektor pertanian, Kementerian Pertanian mengimplementasikan program BEKERJA yang pada intinya merupakan upaya pemberdayaan petani miskin untuk mengembangkan multiusaha pertanian yang meliputi usaha ternak ayam petelur, usaha tanaman sayuran, buah dan perkebunan. Penelitian ini bertujuan untuk memahami bagaimana dampak program tersebut terhadap peningkatan pendapatan dan penurunan kemiskinan petani. Penelitian dilakukan di 11 provinsi pada 38 kabupaten yang merupakan lokasi program bekerja tahun 2018 dan 2019 Data yang digunakan merupakan data primer yang dikumpulkan melalui wawancara dengan petani peserta program. Hasil analisis deskriptif kuantitatif dan kualitatif menyimpulkan bahwa program tersebut berhasil dalam menumbuhkan kegiatan usaha pertanian pada petani miskin, tetapi belum mampu meningkatkan pendapatan petani secara signifikan sehingga jumlah petani miskin peserta program hanya berkurang sebesar 1,48%. Banyak tantangan yang dihadapi dalam memberdayakan petani miskin, oleh sebab itu diperlukan komitmen yang kuat untuk menanggulangi kemiskinan di sektor pertanian. Untuk meningkatkan efektivitas upaya penanggulangan kemiskinan tersebut maka pemberdayaan petani miskin pada masa yang akan datang hendaknya dilaksanakan dengan mempertimbangkan beberapa hal sebagai berikut: (1) komoditas yang dikembangkan difokuskan pada usaha ternak ayam petelur dan sayuran, (2) memberikan bantuan yang berkesinambungan pada sarana produksi utama setidaknya hingga usaha pertanian yang dilakukan petani menguntungkan secara finansial, (3) memperkuat pembinaan teknis budi daya, (4) penetapan petani sasaran dilakukan dengan lebih cermat dan diutamakan pada petani yang berusia relatif muda, dan (5) mengembangkan program khusus yang difokuskan bagi petani miskin.